Pengembangan dan Analisis Kemampuan Peserta Didik dalam Menyelesaikan Soal Statistika Model PISA - Amalia, Eka Nurul; Malasari, Putri Nur (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
One of the problems in learning mathematics is the lack of student's ability to solve story problems. Story questions can provide many benefits for students. Improving mathematical literacy skills is one solution that can be done to overcome this problem. Improvement can be done through a habituation process. Based on the problem description, mathematical literacy questions were developed which could be used as material for students' reflection. This research uses a design research approach with preliminary research stages, a prototyping stage, summative evaluation, and systematic reflection and documentation. The mathematical literacy question instrument that had been developed was also validated by two validators and the results were very valid. Next, the instrument was tested on class VIII students at one of the MTs in Kudus, and the majority of students had low mathematical literacy skills. This condition also influences the low ability of students to solve story problems. Based on the research results, it is necessary to carry out more intensive training in mathematics learning.